Growth Hormone, Insulin-Like Growth Factor-1, Insulin Resistance, and Leukocyte Telomere Length as Determinants of Arterial Aging in Subjects Free of Cardiovascular Diseases - Strazhesko, Irina D.; Tkacheva, Olga N.; Akasheva, Dariga U.; Dudinskaya, Ekaterina N.; Plokhova, Ekaterina V.; Pykhtina, Valentina S.; Kruglikova, Anna S.; Brailova, Natalia V.; Sharashkina, Natalia V.; Kashtanova, Daria A.; Isaykina, Olesya Y.; Pokrovskaya, Mariya S.; et al. (Frontiers in Genetics, 2017)
Background: Increased arterial stiffness (AS), intima-media thickness (IMT), and the presence of atherosclerotic plaques (PP) have been considered as important aspects of vascular aging. It is well documented that the cardiovascular system is an important target organ for growth hormone (GH) and insulin-like growth factor (IGF)-1 in humans, and GH /IGF-1 deficiency significantly increases the risk for cardiovascular diseases (CVD). The telomere length of peripheral blood leukocytes (LTL) is a biomarker of cellular senescence and that has been proposed as an independent predictor of (CVD). The aim of this study is to determine the role of GH/IGF-1, LTL and their interaction cardiovascular risk factors (CVRF) in the vascular aging. Methods: The study group included 303 ambulatory participants free of known CVD (104 males and 199 females) with a mean age of 51.8 ± 13.3 years. All subjects had one or more CVRF [age, smoking, arterial hypertension, obesity, dyslipidemia, fasting hyperglycemia, insulin resistance—HOMA (homeostatic model assessment) >2.5, or high glycated hemoglobin]. The study sample was divided into the two groups according to age as “younger” (m ≤ 45 years, f ≤ 55 years) and “older” (m > 45 years, f > 55 years). IMT and PP were determined by ultrasonography, AS was determined by measuring the carotid-femoral pulse wave velocity (c-f PWV) using the SphygmoCor system (AtCor Medical). LTL was determined by PCR. Serum IGF-1 and GH concentrations we measured by immunochemiluminescence analysis. Results: Multiple linear regression analysis with adjustment for CVRF indicated that HOMA, GH, IGF-1, and LTL had an independent relationship with all the arterial wall parameters investigated in the younger group. In the model with c-f PWV as a dependent variable, p < 0.001 for HOMA, p = 0.03 for GH, and p = 0.004 for LTL. In the model with IMT as a dependent variable, p = 0.0001 for HOMA, p = 0.044 for GH, and p = 0.004 for IGF-1. In the model with the number of plaques as a dependent variable, p = 0.0001 for HOMA, and p = 0.045 for IGF-1. In the older group, there were no independent significant associations between GH/IGF-1, LTL, HOMA, and arterial wall characteristics. Conclusions: GH/IGF-1, IR, HOMA, and LTL were the important parameters of arterial aging in younger healthy participants.